2021
DOI: 10.3389/fpls.2021.632676
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic Acid Regulates the Root Growth Trajectory by Reducing Auxin Transporter PIN2 Protein Levels in Arabidopsis thaliana

Abstract: The root is in direct contact with soil. Modulation of root growth in response to alterations in soil conditions is pivotal for plant adaptation. Extensive research has been conducted concerning the adjustment of root elongation and architecture in response to environmental factors. However, little is known about the modulation of the root growth trajectory, as well as its hormonal mechanism. Here we report that abscisic acid (ABA) participated in controlling root growth trajectory. The roots upon ABA treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…As crucial regulators of plant growth and development, interactions between phytohormones occur frequently. Such interactions, often referred to as ‘crosstalk’, without defining any specific mechanisms, have been reported widely [ 12 , 96 98 ], e.g. between ABA and other phytohormones, including auxins, gibberellins (GAs), ethylene, and jasmonic acids (JAs) [ 3 , 4 , 7 ].…”
Section: Interactions Between Aba and Other Phytohormonesmentioning
confidence: 99%
“…As crucial regulators of plant growth and development, interactions between phytohormones occur frequently. Such interactions, often referred to as ‘crosstalk’, without defining any specific mechanisms, have been reported widely [ 12 , 96 98 ], e.g. between ABA and other phytohormones, including auxins, gibberellins (GAs), ethylene, and jasmonic acids (JAs) [ 3 , 4 , 7 ].…”
Section: Interactions Between Aba and Other Phytohormonesmentioning
confidence: 99%
“…We concluded that by regulating the expression of PIN2 and the degradation of PIN2 protein, high levels of SA impaired PIN2-dependent auxin transport and inhibited root hair growth. Differently, exogenous ABA application reduced the intensity of membrane PIN2 by suppressing PIN2 expression rather than by accelerating PIN2 degradation to elicit the waving root growth trajectory [ 43 ]. At a concentration of 100 μM, SA stimulated PIN2 hyperclustering during gravitropism [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PR inhibition by ABA requires intact auxin transport and signalling, whereas LR elongation does not (Emenecker and Strader 2020). The interaction between ABA and auxin in RSA is complex, as auxin polar transport is responsible for auxin movement in plants, and ABA alters the expression of auxin transporters (Brady et al 2003;Sun et al 2018;Xie et al 2021). Moreover, ABA interferes with auxin transport.…”
Section: Abscisic Acid-auxin Interactionsmentioning
confidence: 99%
“…Therefore, these results suggest that auxin works downstream of ABA in root elongation. Recently, it was found that exogenous ABA reduces the expression of PIN2 an auxin transporter (Xie et al 2021).…”
Section: Introductionmentioning
confidence: 99%